Google Sites Interactive Multimedia to Improve Information Literacy of Elementary School Students - Sri Wahyuningsih; Aprilia Tina Lidyasari (International Journal of Elementary Education, 2025)
The learning process in the Industry 4.0 era, which is inseparable from information technology, makes information literacy an essential factor that students must possess. This study aims to develop Google Sites-based interactive multimedia to improve students’ information literacy. The approach used in this study is Research and Development (R&D) with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research subjects consisted of 36 sixth-grade elementary school students. The sampling technique used was purposive sampling. The data collection methods used in this study were questionnaires and tests, with instruments consisting of a Likert scale and information literacy tests. The collected data were then analyzed using descriptive statistical methods. The analysis results showed that the Google Sites-based interactive multimedia received scores of 92.5 from media experts, 91.49 from content experts, 95.72 from teachers, and 88.63 from students. Furthermore, the t-test showed a significance value (2-tailed) of 0.000 < 0.05, indicating a significant difference between the experimental group and the control group. The mean difference of 17.778 indicates that the experimental group had an average information literacy score 17.778 points higher than the control group. Thus, it can be concluded that Google Sites-based interactive multimedia is highly feasible for use in learning and effective in improving students’ information literacy.